2016
DOI: 10.4103/0973-6131.183707
|View full text |Cite
|
Sign up to set email alerts
|

Impact of individualized yoga therapy on perceived quality of life performance on cognitive tasks and depression among Type II diabetic patients

Abstract: Context:An individualized approach of providing yoga support can address many of the disease-related concerns indicated in the management of diabetes, specifically the impact on other life activities and long-term functional wellbeing.Aim:To analyze the role of regular yoga practice as a self-management approach to achieve glycemic control and psychological wellbeing in Type II diabetic patients.Methods:Ninety-one subjects of both sexes responded to the announcement and consented to participate in the study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…48 Various studies have shown the efficacy of yoga on glycaemic control, improvement in blood glucose, cholesterol, oxidative stress markers, BP, anthropometric measurements, heart rate, sympathetic activity, coagulation profiles, pulmonary function, reduction in the risk factors for cardiovascular disease and thus its contribution towards health in patients with diabetes. 8,12,18,19,20,21,22,23,24,25,49 A systematic review of controlled trials performed on the effect of yoga on type 2 DM revealed that yoga produced significant effect on various parameters in DM treatment and prevention. These factors include glycaemic control (FBG, postprandial blood glucose [PPBG], fasting insulin and HbA1c), insulin resistance, reduction in low-density lipoprotein (LDL) and increase in high-density lipoprotein (HDL), reduction in waist-to-hip ratio and reduction in BP.…”
Section: Yoga and Type 2 Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Various studies have shown the efficacy of yoga on glycaemic control, improvement in blood glucose, cholesterol, oxidative stress markers, BP, anthropometric measurements, heart rate, sympathetic activity, coagulation profiles, pulmonary function, reduction in the risk factors for cardiovascular disease and thus its contribution towards health in patients with diabetes. 8,12,18,19,20,21,22,23,24,25,49 A systematic review of controlled trials performed on the effect of yoga on type 2 DM revealed that yoga produced significant effect on various parameters in DM treatment and prevention. These factors include glycaemic control (FBG, postprandial blood glucose [PPBG], fasting insulin and HbA1c), insulin resistance, reduction in low-density lipoprotein (LDL) and increase in high-density lipoprotein (HDL), reduction in waist-to-hip ratio and reduction in BP.…”
Section: Yoga and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Studies have demonstrated the effectiveness of yoga and meditation in type 2 DM in various ways such as reducing fasting blood glucose (FBG) and glycosylated haemoglobin, improving lipid profile, improving BP and waist-to-hip ratio, reducing inflammatory, oxidative and psychological stress markers, improving depression and cognitive task performance, thus improving the QOL of patients. 12,18,19,20,21,22,23,24,25 Physical activities like aerobic and resistance exercises have also shown improvements in type 2 DM patients by improving glycaemic control and reducing the risk factors linked with cardiovascular pathologies. 15,26,27 The purpose of this study was to review analytically the data available on the effectiveness of yoga and other physical activities in type 2 DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 6 7 ] Some studies suggest the role of yoga in the management of diabetes and other conditions. [ 8 9 ] The promising benefits of yoga interventions for T2-DM have also been recorded in a recent systematic review. [ 7 ] Collectively, findings suggest that yogic practices may promote significant improvements in several indices in T2-DM management, including glycemic control, lipid levels, and body composition and overall quality of life of diabetes patients.…”
Section: Introductionmentioning
confidence: 99%